Calcitriol Alleviates MPP+- and MPTP-Induced Parthanatos Through the VDR/PARP1 Pathway in the Model of Parkinson’s Disease - Hu, Junjie; Wu, Jiawei; Wan, Fang; Kou, Liang; Yin, Sijia; Sun, Yadi; Li, Yunna; Zhou, Qiulu; Wang, Tao (Frontiers in Aging Neuroscience, 2021)
The pathogenesis of Parkinson’s disease (PD) is currently unclear. Recent studies have suggested a correlation between vitamin D and PD. Vitamin D and its analogs have protective effects in animal models of PD but these studies have not clarified the mechanism. Parthanatos is a distinct type of cell death caused by excessive activation of poly (ADP-ribose) polymerase-1 (PARP1) and the activation of PARP1 in PD models suggests that parthanatos may exist in PD pathophysiology. 1,25-dihydroxyvitamin D3 (calcitriol) is a potential inhibitor of PARP1 in macrophages. This study aimed to investigate whether calcitriol treatment improves PD models and its effects on the parthanatos pathway. A 1-methyl-4-phenylpyridinium (MPP+) -induced cell model and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) subacute animal model were selected as the in vitro and in vivo PD models, and calcitriol was applied in these models. Results showed that parthanatos existed in the MPP+-induced cell model and pretreatment with calcitriol improved cell viability, reduced the excessive activation of PARP1, and relieved parthanatos. The application of calcitriol in the MPTP subacute animal model also improved behavioral tests, restored the damage to dopamine neurons, and reduced the activation of PARP1-related signaling pathways. To verify whether calcitriol interacts with PARP1 through its vitamin D receptor (VDR), siRNA and overexpression plasmids were used to downregulate or overexpress VDR. Following the downregulation of VDR, the expression and activation of PARP1 increased and PARP1 was inhibited when VDR was overexpressed. Co-immunoprecipitation verified the combination of VDR and PARP1. In short, calcitriol can substantially improve parthanatos in the MPP+-induced cell model and MPTP model, and the protective effect might be partly through the VDR/PARP1 pathway, which provides a new possibility for the treatment of PD.